EFFECT OF RATIO OF YELLOW WATERMELON FLESH (CITRULLUS VULGARIS S.) AND SECANG WOOD EXTRACT (CAESALPINIA SAPPAN L.) ON THE QUALITY OF WATERMELON ALBEDO SHEET JAM - Syarifah Nabila; Oke Anandika Lestari; Yohana Sutiknyawati Kusuma Dewi (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2026)
Sheet jam is a semi-solid jam that is modified into a sheet shape according to the surface of the bread with an elastic and compact texture, one of which can be made from yellow watermelon albedo. Watermelon albedo, which is usually discarded, contains pectin which functions to form a gel. Sappan wood (Caesalpinia sappan L.) is used as a natural dye, producing yellow at acidic pH and red at neutral pH. Watermelon flesh can provide a natural fruit flavor (taste). This study aims to obtain the ratio of yellow watermelon flesh to sappan wood extract which has the best physicochemical and sensory characteristics of sheet jam. Randomized Block Design (RBD) with one factor, namely five ratios of watermelon flesh and sappan wood extract, 100%: 0%, 75%: 25%, 50%: 50%, 25%: 75%, and 0%: 100%, each repeated five times. The best results were obtained at the ratio of watermelon flesh: sappanwood extract 75%:25% with a water content of 11.87%, reducing sugar 42.96%, color L* 40.07, a* 4.03, b* 4.10, total acid 1.66%, and sensory taste sweet, chewy texture, yellow watermelon aroma, yellow color and overall preference more. The presence of sappanwood extract can reduce the use of fruit flesh.